Hexagonally packed Pd nanoarray catalyst for liquid-phase enantioselective hydrogenation of acetophenone to R-(+)-1-phenylethanol in the presence of S-proline - Chen, X; Lou, Z; Qiao, M; Fan, K; Tsang, S; He, Y (2008)
Hexagonally packed Pd nanoarray catalyst was prepared via the "two solvents" strategy with mesoporous molecular sieve SBA-15 as a hard template. By using S-proline as the chiral modifier, the catalyst exhibited superior activity and selectivity in liquid-phase hydrogenation of acetophenone to R-(+)-1-phenylethanol with up to 100% chemoselectivity and 28.8% enantiomeric excess. The presence of S-proline and the regular hexagonal mesostructure of the Pd nanoarray catalyst are crucial for its superior catalytic performance. © 2008 American Chemical Society.